EVALUATION COMPARISON IMAGE QUALITY OF BREATH HOLD (SSTSE) AND RESPIRATORY TRIGGERING (TSE) TECHNIQUE TO THE EXAMINATION OF MAGNETIC CHOLANGIOPANCREATOGRAPHY (MRCP) - Suroiyah, Nikky Anis; Latifah, Risalatul; Utomo, Sri Andreani (Journal of Vocational Health Studies, 2017)
Background: Magnetic resonance cholangiopancreatography (MRCP) is MRI examination to visualize to visualize a disorder in part biliary or of the human bile. The artefact in the image MRCP is often happened due to the movement of respiratory system. Purpose:  This study to compare the better image quality between Breath Hold (SSTSE) and Repiratory Triggering (TSE)techinques. Method: This study used observational analytic study with prospective approach. 16 samples were examined with two techniques SSTSE and TSE respectively in order to get 3D MRCP image. The Signal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR) is measured to evaluate the image quality. Result: The SSTSE technique only has a higher SNR in gallbladder meanwhile the TSE technique has a higher SNR in pancreatic duct. The higher CNR is got using TSE technique. Conclusion:  The TSE showed the higher SNR in pancreatic duct and the higher CNR is got with SSTSE technique. The recommendation technique for evaluating pancreatic duct is respiratory triggering.